Strategies to Improve the Performance of Micro, Small, and Medium Enterprises Damariz Snack and Catering Magelang City - Dinda Safitri; Vira Marinda; Luna Mayang Anandira; Archie Zakkharia Dakarwan Putra (Equity: Jurnal Ekonomi, 2024)
This article is motivated by the phenomenon of a number of MSMEs that ignore the management system in building strategies so that they face various problems and have less than optimal performance. This study aims to provide strategic solutions to improve the performance of MSME Damariz through an in-depth analysis of internal and external factors that affect their operations. The main focus is to develop strategies that can be implemented practically to face existing challenges and take advantage of available opportunities. In this context, research not only functions as an evaluation tool, but also as a strategic guide for better decision making. This study uses a qualitative descriptive approach, which is based on primary and secondary data collection. Primary data was collected through in-depth interviews and direct observations with MSME owners to get a real picture of operational conditions and directly understand the problems in MSMEs directly. Secondary data was obtained from scientific journals and related books as references to build a strong theoretical foundation. The findings of this study indicate that MSME Damariz has unexplored opportunities with the aim of improving performance from identifying potential and providing strategic recommendations. SWOT analysis is used as an analytical tool in this study using the IFE, EFE, and IE matrices. As a supporter of this research, the IE matrix table is depicted in cell V, where horizontal integration occurs, which means that there is a need to improve strategies in supporting Damariz MSMEs.